Alzheimer's disease and the law: positive and negative consequences of structural stigma and labeling in the legal system. (2nd November 2017) - Werner, Perla; Doron, Israel (Issi)
ABSTRACT: Objective: To explore the meaning and consequences of labeling on structural stigma in the context of Alzheimer's disease (AD) in the legal system. Method: This qualitative study was made up of three focus groups including social workers and lawyers ( n = 26). Participants were asked to report their experience in circumstances in which persons with AD and their family members engage with the legal system. Thematic analysis using the constant comparative method was used. Results: The discussions in the focus groups raised two overall themes. (1) The significance of the medical diagnostic labeling of AD in the legal system and (2) the consequences of labeling of AD within the legal system. This last theme included four sub-themes: (a) negative consequences of labeling; (b) reasons associated with negative consequences of labeling; (c) positive consequences of labeling; and (d) reasons associated with positive consequences of labeling. Conclusion: Findings of the study provide a first foundation for future research on the meaning and consequences of labeling in legal cases involving persons with AD. They suggest that increasing judges' knowledge about AD and reforming the existing 'status-based' legal capacity legislation might benefit by limiting the legal weight given today to the medical diagnosis.